2011
DOI: 10.1103/physics.4.7
|View full text |Cite
|
Sign up to set email alerts
|

A useful pyramid scheme

Abstract: Our ab initio theory calculations predict a semiconducting band structure of I-Mn-V compounds. We demonstrate on LiMnAs that high-quality materials with group-I alkali metals in the crystal structure can be grown by molecular beam epitaxy. Optical measurements on the LiMnAs epilayers are consistent with the theoretical electronic structure. Our calculations also reproduce earlier reports of high antiferromagnetic ordering temperature and predict large, spin-orbit-coupling-induced magnetic anisotropy effects. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…The work has experimentally demonstrated the feasibility of a spintronic concept [3][4][5] in which the electronic device characteristics are governed by the staggered magnetization axis in an AFM. It has been shown that the AFM moments can be manipulated via an exchange-coupled ferromagnet (FM) 1,2,6 and that the AFM magnetoresistance signals can persist to room temperature 6 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The work has experimentally demonstrated the feasibility of a spintronic concept [3][4][5] in which the electronic device characteristics are governed by the staggered magnetization axis in an AFM. It has been shown that the AFM moments can be manipulated via an exchange-coupled ferromagnet (FM) 1,2,6 and that the AFM magnetoresistance signals can persist to room temperature 6 .…”
mentioning
confidence: 99%
“…Although a ferromagnetic ground state is rare within magnetic materials derived from semiconductor compounds and their Curie temperatures are below room temperature, high Néel temperature (T N ) AFMs can be found, for example, among the magnetic counterparts of the I-II-V semiconductors (see also Supplementary Table S1 and Supplementary Note 1) 4,5 . The structures of the non-magnetic semiconductors such as LiZnAs, NaZnAs, CuZnAs and AgZnAs are closely related to the III-V zincblende structure, as shown in Fig.…”
mentioning
confidence: 99%
“…78,79 The synthesis of semiconductors with high-temperature ferromagnetic ordering of spins, which would simultaneously enable the conventional tunability of electronic properties and spintronic functionalities, remains a significant challenge. In previous sections we already mentioned examples of metal antiferromagnets which have so far driven much of the research in antiferromagnetic spintronics.…”
mentioning
confidence: 99%
“…On the other hand, robust AFM ordering occurs much more frequently in nature than FM ordering, particularly in conjunction with semiconducting electronic structure 9,10 . Recent studies have identified several candidate AFM semiconductor materials, ranging from AFM counterparts of common zinc-blende or half-Heusler compound semiconductors [11][12][13][14] to perovskite semiconductor-AFM oxides [15][16][17][18][19] . A particular focus in this materials research has been on the preparation of thin epitaxial films and heterostructures 11,13,18,19 as a prerequisite for the envisaged spintronic devices.…”
mentioning
confidence: 99%